Status Hak Atas Tanah Dan Bangunan Yang Didirikan Di Atas Lahan Ruang Terbuka Hijau - Muhammad Syahri Ramadhan (Institut Agama Islam Negeri Metro, 2018)
Abstract There are still many communities to occupy a region that are not be established a building, one of them is the green open space. It is equal to the happened to some locals the way of demang lebar daun and hulubalang I build the building on the green open space. This research in a research juridical empirical with the approach case study and observation. Basically a mechanism determine area of green open space are introduced and effected in accordance with Article 53 (1) of Law No. 5 of 1960 on Basic Provisions of Agrarian in status for land and building rights founded by residents demang hulubang i and the wide leaves is the right riding in. But, legally protection for the located in space could not be realised but of basic human and respect the rights of the community, if the land will be required the government will give a letter advance notice to the community to empty and even move their homes the fixed term.